(untitled) (Research, Society and Development, 2024)
The aim of this study was to carry out a bibliometric analysis of the use of the Turiaçu pineapple cultivar and its by-products in the area of Food and Nutrition. Queries were carried out in the databases Periódicos Capes, Google Scholar and Web of Science, using the terms “abacaxi”, “pineapple”, “ananas” and “Turiaçu as keywords, using the entire body of the studies to analyze the variables authors, year of publication, institution where the study was carried out, part of the cultivar used in the study, place where the cultivar was obtained, objectives and results. Thirteen studies were selected, the Universidade Estadual (n=5) and Universidade Federal (n=4) of Maranhão were the institutions with the highest number of papers, the city of Turiaçu in Maranhão (n=6), followed by Itacoatiara in Amazonas (n=3) were the main places where the authors obtained the fruit analyzed in the studies, most of the studies evaluated the whole fruit (n=8), followed by the pulp (n=3) and peel (n=2), and it was found that the analyses were concentrated in 5 areas, with emphasis on physicochemical (n=8) and biometric (n=4) analyses. It can be concluded that although the cultivar originated in the state of Maranhão, there is a growing movement of research and production to the state of Amazonas, with emphasis on the Novo Remanso Indication of Origin (IP) conferred on the Turiaçu cultivar, there is also a low number of research studies, demonstrating that it is a promising cultivar for the development of studies in the area of Food and Nutrition.